Modeling of Enterprise Potential for Development of Management Strategies - Kosteniuk, Iu. B. (Statistics of Ukraine, 2019)
The conducted research is concerned with the evaluation of various elements of the potential and the determination of their influence on the competitive behavior of the enterprise. Using the graphical method "Polygon of potential" the efficiency of various elements of the enterprise potential is determined. The performed modeling makes it possible to systematically establish quantitative and qualitative links between individual elements of the potential, the level of its development and competitiveness and on that basis to justify and timely implement strategies for managing the enterprise potential. In practice, it is difficult to use a spherical form to evaluate the potential of the enterprise. The purpose of the analysis is to simplify the graphical model to the form of a square according to the number of directions diagnostics of potential capabilities for the enterprise. Diagnosis of the enterprise potential was performed by the method of comparative complex rating estimation with the help of the system of indicators for the following functional blocks: production potential; financial potential; staff potential; innovative potential. The calculation of the final rating is based on the method of points used to analyze each indicator of these functional blocks. Models based on data over three years have a different square shape. Modeling has helped to identify the disharmony of vectors that describe financial and innovation potential. This potential requires immediate transformation, which will help to improve the balance of the elements of the potential. The results of the study are the proposed strategies for managing the potential of the enterprise: a strategy for improving staff capacity; strategy for improving innovation potential; a strategy for improving financial capacity. In addition, the company needs to pay special attention to the development of innovative potential, which substantiates the success of the company and the high efficiency of innovative business processes.